2013
DOI: 10.1017/s2045796013000693
|View full text |Cite
|
Sign up to set email alerts
|

Life in acute mental health settings: experiences and perceptions of service users and nurses

Abstract: Background. Acute psychiatric provision in the UK today as well as globally has many critics including service users and nurses. Method. Four focus groups, each meeting twice, were held separately for service users and nurses. The analysis was not purely inductive but driven by concerns with the social position of marginalised groups - both patients and staff. Results. The main themes were nurse/patient interaction and coercion. Service users and nurses conceptualised these differently. Service users found nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 24 publications
3
78
0
1
Order By: Relevance
“…Two found that higher levels of experienced coercion were related to lower overall satisfaction (Middelboe et al, 2001;Smith et al, 2014). Qualitative interviews in one study (Rose et al, 2015) describe a pattern of coercion occurring as a result of service users frustrations with the limitations of the ward environment. Further qualitative research has also found that service users perceive satisfaction as being influenced by the fear of violence (Duggins and Shaw, 2006).…”
Section: Coercion and Safetymentioning
confidence: 99%
See 3 more Smart Citations
“…Two found that higher levels of experienced coercion were related to lower overall satisfaction (Middelboe et al, 2001;Smith et al, 2014). Qualitative interviews in one study (Rose et al, 2015) describe a pattern of coercion occurring as a result of service users frustrations with the limitations of the ward environment. Further qualitative research has also found that service users perceive satisfaction as being influenced by the fear of violence (Duggins and Shaw, 2006).…”
Section: Coercion and Safetymentioning
confidence: 99%
“…They also did not score highly regarding representativeness of the sample, mainly due to a failure to report the number of people who had declined to participate, and the associated reasons. Of the qualitative studies, one scored 25% (Duggins and Shaw, 2006) and three scored 50% (Rose et al, 2015;Stewart et al, 2015;Wallace et al, 1999). The qualitative papers generally scored well for reporting the analysis used, but there was little or no acknowledgement of the impact of the researcher on the research process.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, there is intense pressure to discharge patients as quickly as possible to free up beds as inpatient care becomes more and more of a scarce and expensive resource. The majority of nursing time may therefore be spent on responding to crisis and risk management, and on tasks such as paperwork and bed managements which do not involve direct patient contact (Mullen 2009;Rose et al, 2015).…”
Section: "There Are Two Sorts Of 'Boring' On the Ward One Is Caused mentioning
confidence: 99%